The sleepers in the cave - Khan, Saniyasnain (Goodword Kidz : India, 2011)
The tale centers on a group of young men who, during a time of religious persecution, sought refuge in a cave to escape oppression. They fell into a deep sleep and awoke centuries later, finding that the world had changed. This narrative emphasizes themes of faith, trust in Allah, and the miraculous ways in which He protects His believers.